2017
DOI: 10.4314/ijbcs.v10i6.20
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of gamma-glutamyl-transpeptidase activity and uric acid level in mixed chemical exposure: implications for mutagenic and preneoplastic events

Abstract: Mixed chemical toxicity including genotoxicity is currently a major concern in rapidly industrializing developing countries. Simple biomarkers remain a constraint. Gamma-glutamyl-transpeptidase (GGT), a precursor of glutathione, protects against chemical toxicity including genotoxic effects and may serve as a marker for pre-neoplastic lesion. The objective of the study was to determine a possible relationship between GGT, uric acid and the angiogenic agent copper (Cu) in mixed chemical exposure. Sixty-six indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…45 The evidence suggests an association between WEEE exposure and changes in thyroid function, in cellular function and expression, in temperament and behaviour and in adverse neonatal outcomes. 33,37,46,47,48,49 Despite the volumes of WEEE recycled informally, the prevalence of work-related injuries among WEEE workers in Africa is largely unknown. A study assessed for the first time the prevalence, patterns and factors associated with occupational injuries among WEEE workers in the informal sector in Nigeria and symbolic of the African continent.…”
Section: Health Impactsmentioning
confidence: 99%
“…45 The evidence suggests an association between WEEE exposure and changes in thyroid function, in cellular function and expression, in temperament and behaviour and in adverse neonatal outcomes. 33,37,46,47,48,49 Despite the volumes of WEEE recycled informally, the prevalence of work-related injuries among WEEE workers in Africa is largely unknown. A study assessed for the first time the prevalence, patterns and factors associated with occupational injuries among WEEE workers in the informal sector in Nigeria and symbolic of the African continent.…”
Section: Health Impactsmentioning
confidence: 99%
“…Some of these jobs are well-known to expose workers to toxic metals like lead, mercury, chromium, and cadmium, volatile organic compounds (VOCs) like benzene particularly from sources like motor-vehicle exhaust and gasoline-vapor emissions, and skin-irritating substances including oils, greases, solvents, and detergent [9][10][11][12]. Exposure to chemical mixtures, including toxic metals, is a common risk factor for cancer, especially among certain occupational groups, because various substances prevalent in industrial and agricultural environments have been identified as carcinogenic [13][14][15][16][17]. These chemicals can cause DNA damage, resulting in mutations and abnormal cellular behaviour.…”
Section: Introductionmentioning
confidence: 99%